GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 30220 species occurrences available in GBIF matching the query: Country: Lebanon. The dataset includes 30220 records from 280 constituent datasets: 2 records from KUBI Ornithology Collection. 5 records from Collection Malakologie - SNSD. 25 records from Essig Museum of Entomology. 5 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 1 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 12 records from published_chenopodium_vulvaria_observations. 14 records from CAS Ichthyology (ICH). 12 records from Ichthyology Collection - Royal Ontario Museum. 6 records from MVZ Herp Collection (Arctos). 141 records from Carnet en Ligne. 5 records from Invertebrate collections. 1 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 279 records from Invertebrates Collection of the Swedish Museum of Natural History. 7 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 9 records from DSMZ Prokarya Collection Catalogue. 6 records from Global Butterfly Information System (GloBIS). 5 records from UMZC Zoological Specimens. 2 records from Museo Nacional de Ciencias Naturales, Madrid. Colección de Tejidos y ADN. 2 records from Naturalis Biodiversity Center (NL) - Mammalia. 11 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 4 records from University of Florida Invertebrate Paleontology. 110 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 715 records from BioGIS - Birds - INPA database. 1 records from Bryophyte herbarium, Trondheim (TRH). 4 records from The Erysiphales Collection at the Botanische Staatssammlung München. 1631 records from EURISCO, The European Genetic Resources Search Catalogue. 2 records from HUCS - Herbário da Universidade de Caxias do Sul. 2 records from Invertebrata Collection of Institute of Systematics and Evolution of Animals. 3 records from Phytopathogenic Fungi Observed by Hans and Hanna Doppelbaur. 1 records from Academy of Natural Sciences OBIS Mollusc Database. 692 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 10 records from Missouri Botanical Garden. 10 records from Biological and palaeontological collection and observation data MNHNL. 8 records from MfN - Fossil invertebrates IIb. 5 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. 10 records from Estonian University of Life Sciences. 37 records from Herps Specimens. 32 records from Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Formicidae Collection Univesity of Granada. 2 records from AMNH Mammal Collections. 1 records from DSMZ Collection of Filamentous Fungi and Yeasts. 25 records from CZE National PGR Inventory. 11 records from KUBI Vertebrate Paleontology Collection. 500 records from BioGIS - Vascular plants - INPA database. 3 records from Collection Mammalia SMF. 2 records from Diptera. 120 records from MfN - Fossil invertebrates III. 680 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 2 records from Orthopteroidea. 49 records from Field Museum of Natural History (Zoology) Fish Collection. 1 records from URM - Herbário Pe. Camille Torrand. 56 records from Clitellata - SMF. 6 records from UCBG TAPIR Provider. 41 records from Avena wild species collection. (N.I.Vavilov Institute of Plant Genetic Resources (VIR)). 44 records from Natural History Museum, University of Tartu. 44 records from Vertebrate Paleontology Division, Yale Peabody Museum. 4 records from Bernice P. Bishop Museum. 9 records from Herbaria of the University and ETH Zürich. 2068 records from Royal Botanic Garden Edinburgh Herbarium (E). 1 records from UMMZ Birds Collection. 18 records from UF FLMNH Ichthyology. 3 records from iziko South African Museum - Shark Collection (AfrOBIS). 15 records from Collection Thysanoptera SMF. 14 records from SMNS Herpetologie. 1 records from Collection of Coleoptera. 6 records from Bryotropha (Lepidoptera: Gelechiidae) in Western Palaearctic. 83 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 2 records from SPF-Algae - Herbário da Universidade de São Paulo - Coleção de Algas. 46 records from Vascular Plant Herbarium, Oslo (O). 51 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 6 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 2 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 224 records from Geneva Herbarium – General Collection (G). 6 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 101 records from SINGER Coordinator. 5 records from Field Museum of Natural History (Zoology) Bird Collection. 12 records from Paleobotany Division, Yale Peabody Museum. 46 records from Reptiles and Amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Therevid PEET Project. 1 records from Colección Alberto Tinaut (Formicidae). 6 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 2 records from The Vascular Plant Collection at the Herbarium Tubingense. 47 records from BioGIS - Mammals - INPA database. 69 records from Coleoptera types of John Sahlberg. 15 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 1 records from Naturhistorisches Museum Mainz, Botanical Collection. 9 records from Harvard University Herbaria. 10 records from NPL collections. 6 records from pins. 135 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 14 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 9 records from BioGIS - Mammals - SPNI. 4 records from BioGIS - Fish - HUJ collections. 18 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 18 records from Invertebrate Zoology Division, Yale Peabody Museum. 96 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 5 records from Estonian Museum of Natural History. 11 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 1 records from Lichen Herbarium Berlin. 14 records from Naturalis Biodiversity Center (NL) - Mollusca. 16 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 56 records from Naturalis Biodiversity Center (NL) - Crustacea. 154 records from SMNS Palaeontological collection - Cretaceous and jurasic invertebrates. 69 records from Lund Botanical Museum (LD). 13 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 18 records from Mammalogy Collection - Royal Ontario Museum. 11 records from BioGIS - Land snails - HUJ collections. 2 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 1100 records from Natural History Museum (London) Collection Specimens. 5 records from Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 5 records from Herbarium Senckenbergianum (FR). 55 records from Botany (UPS). 35 records from Collection Mollusca SMF. 199 records from Snow Entomological Museum Collection. 8 records from Collection Bryozoa SMF. 3 records from Bee Biology and Systematics Laboratory. 2 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 31 records from Lund Museum of Zoology - Insect collections (MZLU). 44 records from CAS Herpetology (HERP). 50 records from Collection Pisces SMF. 15 records from Collection Crustacea SMF. 497 records from SMNS Palaeontological collection - Amber. 5 records from SMNK Mantid Collection. 1 records from Jardin botanique de Montréal (JBM). 48 records from Swiss Psyllid (Hemiptera) Collections - Basel. 35 records from Australia's Virtual Herbarium. 4 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Types. 1 records from Royal Museum of Central Africa - True Fruit Flies (Diptera, Tephritidae) of the Afrotropical Region (ENBI wp13). 32 records from ECatSym: Electronic World Catalog of Symphyta. 13 records from CUMV Mammal Collection (Arctos). 1 records from Botanic Garden of the Finnish Museum of Natural History. 25 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 3 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 1 records from Lund Museum of Zoology (MZLU). 40 records from AntWeb. 49 records from Museo Nacional de Ciencias Naturales, Colección de Malacología. 50 records from invertebratezoology. 1 records from Herpetology. 2 records from CABI Bioscience Genetic Resource Collection. 6 records from Fish specimens. 1 records from Palaeontologische Sammlung der Freien Universitaet Berlin. 6 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 1 records from Collection Vermes - ZMB. 1494 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 38 records from Geneva Herbarium – Boissier's Flora Orientalis (G-BOIS). 70 records from Biologiezentrum Linz. 10 records from The Vascular Plant Collection at the Herbarium MSB, Universität München. 10 records from Collection Francaise de Bacteries Phytopathogenes. 2 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Herpetology. 1 records from Collection Herpetology SMF. 2 records from MUST, Insecta. 2 records from Naturalis Biodiversity Center (NL) - Lepidoptera. 17 records from Naturalis National Natural History Museum (NL) – Crustacea_Decapoda. 202 records from Paleobiology Database. 5 records from MfN - Fossil plants (Mesophytic). 2 records from BioGIS - Israeli Lepidopterists Society. 1 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 7 records from Homoptera. 7 records from Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from HBGSpermatophyta - Herbarium Hamburgense. 12 records from Polish gene bank – passport data of plants accessions which are important in human life. 5 records from DORSA - German Orthoptera Collections. 92 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 24 records from MfN - Fossil vertebrates IV. 4 records from Algae herbarium, Trondheim. 2 records from Hymenoptera. 24 records from Fishbase. 1 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 5 records from Palaeobiology collection, FAU Erlangen. 23 records from Geologisch-Paläontologische Sammlung Universität Leipzig. 411 records from Naturalis Biodiversity Center (NL) - Botany. 6 records from University of California Museum of Paleontology. 8 records from CUMV Bird Collection (Arctos). 3 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 1 records from The AAU Herbarium Database. 18 records from Herpetology. 4 records from Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 460 records from Museum of Comparative Zoology, Harvard University. 15 records from iNaturalist research-grade observations. 5 records from CABI Bioscience Fungus Collection. 32 records from KUBI Ichthyology Collection. 11 records from Amphibians and Reptiles collection at the Natural History Museum of Denmark (SNM). 5 records from Fossil (WSHN-FO). 1 records from Collection Crustacea - ZMB. 1 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 1 records from UMMZ Herpetology Collection. 14 records from Harold W. Manter Laboratory of Parasitology Collection. 138 records from Natural History Museum, Vienna - Herbarium W. 12 records from BioGIS - Bryophytes - HUJ collections. 67 records from Diveboard - Scuba diving citizen science observations. 5 records from Collection Polychaeta SMF. 156 records from MfN - Fossil invertebrates Ia. 1 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 1 records from Collection Trichoptera - SMF. 412 records from United States National Plant Germplasm System Collection. 1 records from Christopher Walker collection of Glomeromycotan fungi. 2 records from WFVZ Bird Collections. 5 records from Australian National Herbarium (CANB). 2 records from UA Herbarium. 44 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 1 records from IPK Genebank. 70 records from Australian Museum provider for OZCAM. 2 records from Collection entomologique Pierre Lachiver. 714 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 6690 records from Fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 36 records from Michigan State University Herbarium Lichens. 1 records from The avian collection at the Natural History Museum, Oslo, Norway. 7 records from Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from CUMV Reptile Collection (Arctos). 410 records from EOD - eBird Observation Dataset. 1 records from Diptera Collection of Museum and Institute of Zoology PAS. 13 records from AMNH Herpetology Collections. 3 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 112 records from Field Museum of Natural History (Zoology) Mammal Collection. 28 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 184 records from Herbarium Berolinense. 2 records from Western Palearctic migratory birds in continental Africa. 2 records from Wilson Botanical Garden - Las Cruces Biological Station. 88 records from RBINS collections. 3 records from The Collection of Fungi of the Real Jardín Botánico of Madrid (MA-Fungi). 90 records from SysTax - Zoological Collections. 10 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 11 records from University of Vienna, Institute for Botany - Herbarium WU. 7 records from INRA-Versailles Arabidopsis natural variants. 4 records from BioGIS - Vascular plants - HUJ Herbarium. 178 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 27 records from Invertebrate Paleontology Division, Yale Peabody Museum. 1 records from CAS Invertebrate Zoology (IZ). 5 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 1 records from USU-UTC Specimen Database. 2 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 30 records from Ichthyology. 4 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 49 records from Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC. 5 records from Mammals housed at MHNG, Geneva. 23 records from Collection Arachnology SMF. 1 records from Reptiles, Amphibians and Fishes collection (ZA) in the Comparative Anatomy Collection of the Muséum national d'Histoire naturelle (MNHN - Paris). 49 records from Fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Mosses (S). 45 records from AMNH Bird Collection. 9 records from Mammal specimens. 1744 records from NMNH occurrence DwC-A. 18 records from BioGIS - Fish - INPA database. 9 records from Naturhistorisches Museum Mainz, Zoological Collection. 214 records from Cryptogamy collection (PC) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 73 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 2 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 3 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 7 records from Lepidoptera - SNSD. 85 records from Illinois Natural History Survey Insect Collection. 1 records from NSW herbarium collection. 39 records from SMNS Palaeontological collection - Fossil fishes and marine reptiles. 4 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 3 records from Bohart Museum of Entomology, UCD. 1 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 40 records from BioGIS - Reptiles - INPA database. 6 records from OHN. 5 records from Tiroler Landesmuseum Ferdinandeum. 39 records from Fungi (S). 4 records from Natural History Museum Rotterdam (NL) - Insecta collection. 889 records from Phanerogamic Botanical Collections (S). 1 records from Nordic Genetic Resources. 2 records from Collection Crustacea - SNSD. 1 records from University of Florida Vertebrate Paleontology. 2 records from Ichthyology, Kagoshima University Museum. 75 records from Dataflos. 1 records from LACM Vertebrate Collection. 1981 records from The System-wide Information Network for Genetic Resources (SINGER). 6 records from BioGIS - Vascular plants - Israeli Gene Bank. 2 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 36 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 76 records from Geographically tagged INSDC sequences. 1 records from PRECIS. 5 records from Japan Collection of Microorganisms, RIKEN BioResource Center. 1 records from Lichen herbarium, Oslo (O). 18 records from MVZ Mammal Collection (Arctos). 2 records from William Nylander lichen collection. 497 records from SMNS Palaeontological collection - Amber. 141 records from MAL.
Keywords: GBIF; biodiversity; species occurrences